Mitochondrial Genetics and Epigenetics in Osteoarthritis - Rego-Pérez, Ignacio; Durán-Sotuela, Alejandro; Ramos-Louro, Paula; Blanco, Francisco J. (Frontiers in Genetics, 2020)
During the last years, it has been consistently demonstrated the significant influence of mitochondria in osteoarthritis (OA), the most common joint disease. Not only in terms of mitochondrial dysfunction, but also the mitochondrial genetic polymorphisms, specifically the mitochondrial DNA haplogroups, have been shown to have an important influence in different OA-related features, including prevalence, severity, incidence and progression of the disease. This influence could be probably mediated by the role of mitochondria in the regulation of different processes that are involved in the pathogenesis of OA, such as energy production, generation of reactive oxygen and nitrogen species, apoptosis or inflammation. The regulation of these processes is, at least, partially controlled by the bi-directional communication between nucleus and mitochondria, that permits, not only to maintain the cellular homeostasis, but also to regulate adaptation to a wide range of stressors. This bi-directional communication consists in an “anterograde regulation”, by which the nucleus regulates mitochondrial biogenesis and activity, and a “retrograde regulation”, by which both mitochondria and mitochondrial genetic variation maintain a regulatory signaling control over the nuclear epigenome that leads to the modulation of nuclear genes. Throughout this mini review, we will describe the evidences that demonstrate the profound influence of the mitochondrial genetic background in the pathogenesis of OA, as well as its influence in the nuclear DNA methylome of the only cell type present in the articular cartilage, the chondrocyte. Evidences that lead to seriously consider the mitochondrion as an important therapeutic target in OA